PENGEMBANGAN E-MAGAZINE TEMA PRODUK JAMU NATURNA PADA MATERI UNSUR, SENYAWA DAN CAMPURAN - Buana, Diva Puspita; Astid Putera, Dwi Bagus Rendy; Tamam, Badrud; Qomaria, Nur; Hartiningsih, Try (Natural Science Education Research, 2024)
This study aims to determine the feasibility of the e-Magazine learning media with the theme of herbal medicine products on elemental, compound and mixed materials. The development model uses the ADDIE model. From the results of data acquisition, calculation and analysis, for media validity get an average score of 1.00 with very high criteria and for the validity of the material get an average score of 1.00 with very high criteria. The results of the study show that the e-Magazine learning media with the theme of jamu naturna products has met the eligibility criteria with a very high category. Based on the results, it shows that the e-Magazine media developed is said to be suitable for use as a learning medium in schools